Capacity planning of the registration server in cloud storage. (2017) - Gu, Rui; Jin, Shunfu; Wu, Haixing
Cloud storage is one of the key services in cloud computing. In order to appeal more users to the cloud storage, free cloud experience is provided to potential users. A registration server is set specially for intentional users who are satisfied with the free experience and want to register as very important persons (VIPs). In order to mathematically evaluate the system performance and optimally plan the registration server, we establish a queueing network-based system model. We analyse the steady-state distribution of the system model and derive the performance measures of the system in terms of the average response time of potential users and the utilisation of registration server. For balancing different performance measures, we establish a cost function and develop an optimisation algorithm to plan the capacity of the registration server with a reasonable service rate.